Ecological Characteristics Study of the Vegetation Cover for the Protected Area Faculty of Agriculture at the University of Tripoli-Libya - Malakalrahma Abdurazag Alftisi; Raneem Banur Osman; Rokaia Mohammed Elalem; Fathi Goma Al-Sghair (Budapest International Research and Critics University, 2019)
The aim of this research was to investigate the vegetation characteristics to determine the dominant species because the selected study area never has been ecologically studied before. The study was carried out in the period from April to the end of May 2018 two trips per week. To achieve the study, two methods were used Quadrat Method and Lines-transect Method. 19 lines-transect were randomly distributed with a length of 50 meters in the study area. A total of 92 quadrats 4 m2 selected for perennial plants and 60 quadrats 1 m2 for annual plants (grasses) were distributed to the Line-transect; all plant species and their numbers that appeared in the quadrat were recorded. Vegetation characteristics (density, frequency, and abundance) and their relative values of each plant species were calculated from quadrat, whereas cover and the relative cover was calculated from Line-transect. The results showed that the highest density in annual plants was 32.1 plant / m2 for Stipacapensis followed by Scabiosaarenaria with 15.6 plants /m2, while in perennial plants was found (14.7 plant / m2) for Plantagoalbicans followed by Helianthemumlippii density with (3.26 plant / m2). The obtained results also showed that S.Arenaria has the highest frequency 80%, then S. capensis with 78.30% in annual plants, in perennial plantsP. albicans has the highest frequency (97.8%) followed by H. lippii with (70.6%). It appears from results obtained that the highest cover recorded was (15.8%) for S. capensis followed by P. albicans (12.4%). From the results, the annual plants have the highest value were 187.92 for plant species S. capensis followed by S. arenaria with 148.8. Through the results obtained, the plantcommunity of the study area is Stipa capensis - Scabiosa arenaria Community.